1995
DOI: 10.1128/aac.39.5.1187
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of various beta-lactam antimicrobial agents against clinical isolates of Escherichia coli and Klebsiella spp. resistant to oxyimino cephalosporins

Abstract: Broth microdilution testing was used to study the activity of several beta-lactam antimicrobial agents, including piperacillin-tazobactam and cefepime, against 108 clinically derived Escherichia coli and Klebsiella sp. strains resistant to oxyimino cephalosporins (i.e., putative extended-spectrum ␤-lactamase producers). On the basis of the percentage of susceptible strains, imipenem (100%), cefotetan (Ն92%), and piperacillin-tazobactam (Ն86%) were the most active agents. Cefepime activity (52 to 64% susceptibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 37 publications
5
31
0
Order By: Relevance
“…Maximum isolates of K.pneumoniae (75.6%) were resistance to ampicillin as comparable with other studies [24]. Cephalosporins, particularly second and third generation have been used to treat Klebsiella pneumoniae infections [25]. Low resistance to second and third generation cephalosporins (63.4%) is seen in our studies compared to (84%) other reports [26].…”
Section: Discussionsupporting
confidence: 69%
“…Maximum isolates of K.pneumoniae (75.6%) were resistance to ampicillin as comparable with other studies [24]. Cephalosporins, particularly second and third generation have been used to treat Klebsiella pneumoniae infections [25]. Low resistance to second and third generation cephalosporins (63.4%) is seen in our studies compared to (84%) other reports [26].…”
Section: Discussionsupporting
confidence: 69%
“…However, inoculum effects in ESBL-producing Klebsiella spp. have been reported for cefepime both in vitro and in vivo (12,29), and they could be due, at least in part, to the hydrolysis of this drug by ESBLs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that an increase in inoculum size can be correlated with an increase in ␤-lactam MICs and a decrease in efficacy in vivo (11,12,29,30). Factors that could contribute to these effects are the number, type, and amount of ␤-lactamases; outer membrane permeability; efflux; number and susceptibility of penicillin-binding protein targets; and phase of growth.…”
Section: Discussionmentioning
confidence: 99%
“…Another viewpoint is that the inoculum effect is important for ESBL-producing organisms and that the MIC alone may give erroneous information. In vitro, the MICs of cephalosporins rise as the inoculum of ESBL-producing organisms increases (184,244,344,391). For example, for a Klebsiella pneumoniae strain producing TEM-26, at an inoculum of 10 5 CFU/ml the cefotaxime MIC was 0.25 g/ml, rising to 64 g/ml when the inoculum rose to 10 7 CFU/ml (391).…”
Section: Need For Clinical Microbiology Laboratories To Detect Esbl Pmentioning
confidence: 99%